Comparative study on characterization and adsorption properties of phosphoric acid activated biochar and nitrogen-containing modified biochar employing Eucalyptus as a precursor. (20th June 2021) - Lu, Ze; Zhang, Hua; Shahab, Asfandyar; Zhang, Kang; Zeng, Huiting; Bacha, Aziz-Ur-Rahim; Nabi, Iqra; Ullah, Habib
Abstract: As a green adsorbent, biochar has attained progressive attention due to its advantages such as high carbon content, high surface area, stable structure, and heavy metals removal through cation exchange capacity. Biochar can be synthesized from the feedstock, agricultural, and organic waste. In this study, the activated biochar (AC) and ammonia modified biochar (NAC) were prepared from Eucalyptus waste by acid activation. The adsorption properties of pure AC and NAC were compared for aqueous Cr(VI) removal. Advanced characterization techniques such as scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR) were used to examine the morphology, elemental composition, and functional groups. Several influencing factors on adsorption processes such as solution pH, adsorption dosage, contact time, and initial concentration were investigated. The ammonia modified biochar (NAC) could remove 85.67% of Cr (VI), whereas 76.73% removal rate was observed for the activated biochar (AC) at an initial concentration of 300 mg/L at pH 2.0 and 25 °C with a dosage of 0.025 g/25 mL. The pseudo-second-order kinetic and Freundlich isotherm adsorption models showed close-fitting for the activated biochar (AC) and the ammonia modified biochar (NAC) adsorption in Cr(VI) equilibrium state. Cr (VI) oxidizes nitrogen and oxygen functional groups on NAC following the conversion into Cr (III). The removal and adsorption mechanism was the coexistence of physical adsorption and chemical reduction examined by FTIR and XPS illustrating Cr(VI) removal. Graphical abstract: Image 1 Highlights: Ammonia modified Eucalyptus biochar exhibit stronger adsorption efficiency. Efficient removal of Cr(VI) takes place at pH 2.0 and 25 °C within 1440 min. Adsorption of pure and ammonia modified biochar was endothermic based on the thermodynamic study. Cr(VI) oxidizes N and O functional groups on ammonia modified biochar (NAC) and transforms them into Cr (III).